FASCICLIN-LIKE 18 Is a New Player Regulating Root Elongation in Arabidopsis thaliana - Allelign Ashagre, Hewot; Zaltzman, David; Idan-Molakandov, Anat; Romano, Hila; Tzfadia, Oren; Harpaz-Saad, Smadar (Frontiers in Plant Science, 2021)
The plasticity of root development represents a key trait enabling plants to adapt to diverse environmental cues. The pattern of cell wall deposition, alongside other parameters, affects the extent and direction of root growth. In this study, we report that FASCICLIN-LIKE ARABINOGALACTAN PROTEIN 18 (FLA18) plays a role during root elongation in Arabidopsis thaliana. Using root-specific co-expression analysis, we identified FLA18 to be co-expressed with a sub-set of genes required for root elongation. FLA18 encodes for a putative extra-cellular arabinogalactan protein from the FLA-gene family. Two independent T-DNA insertion lines, named fla18-1 and fla18-2, display short and swollen lateral roots (LRs) when grown on sensitizing condition of high-sucrose containing medium. Unlike fla4/salt overly-sensitive 5 (sos5), previously shown to display short and swollen primary root (PR) and LRs under these conditions, the PR of the fla18 mutants is slightly longer compared to the wild-type. Overexpression of the FLA18 CDS complemented the fla18 root phenotype. Genetic interaction between either of the fla18 alleles and sos5 reveals a more severe perturbation of anisotropic growth in both PR and LRs of the fla18sos5 double mutant, as compared to the single mutants and the wild-type, under restrictive conditions of high sucrose or high-salt containing medium. Additionally, under salt-stress conditions, fla18sos5 had a small, chlorotic shoot phenotype, that was not observed in any of the single mutants or the wild type. As previously shown for sos5, the fla18-1 and fla18-1sos5 root-elongation phenotype is suppressed by abscisic acid (ABA) and display hypersensitivity to the ABA synthesis inhibitor, Fluridon. Last, similar to other cell wall mutants, fla18 root elongation is hypersensitive to the cellulose synthase inhibitor, Isoxaben. Altogether, the presented data assign a new role for FLA18 in the regulation of root elongation. Future studies of the unique vs. redundant roles of FLA proteins during root elongation is anticipated to shed a new light on the regulation of root architecture during plant adaptation to different growth conditions.